Automatic Generation of Noise-Like or Mode-Locked Pulses in an Ytterbium-Doped Fiber Laser by Using Two-Photon-Induced Current for Feedback - Hsiao-Hua Wu; Pin-Han Huang; Yuan-He Teng; Alexey Zaytsev; Osamu Wada; Ci-Ling Pan (IEEE Photonics Journal, 2018)
We present a simple, reliable, and fast method to automatically generate noise-like or mode-locked pulses in a fiber laser. To generate the targeted pulses, we employed two-photon-induced current from a photocell as the feedback signal to control a set of rotatable wave plates in the laser. The effectiveness of using the two-photon absorption signal to discriminate noise-like pulses from mode-locked pulses is theoretically analyzed and experimentally confirmed. We demonstrate our method by using a dispersion-mapped ytterbium-doped fiber ring laser with nonlinear polarization evolution that can generate either noise-like or mode-locked pulses. The average time to attain the prescribed pulses is within a few minutes.